Adsorção de bifenil na superfície de Si (001) por um método de primeiros princípios - Lima, Claudio Pereira (2007)
In this work we investigated the structural and electronic properties of the adsorption of biphenyl molecules on the Si(001) surface. We use the density functional theory with norm conserving psedopontial formalism. For the exchange-correlation energy we test both the local density and the generalized gradient approximations, where the last approach have been showed to give better results to describe the adsorpotion of a molecule on the Si surface. Our results show that the biphenyl molecule is adsorbed on the Si(001) surface in four different structures. This result is in agreement with experimental data where have been observed at least two different configurations for the biphenyl on the Si(001) surface. The binding energy for the most stable structure of the biphenyl is 2.48 eV. We observe that some molecule bonds with the Si surface are strong, while others on are not. By personating alternating dimer rows of the Si(001) surface with hydrogen atoms, our results show that the structure of the biphenyl on the Si surface keeps almost the same as that of the non-passivated surface. However there is a change of the stability: the most stable structure for the biphenyl on the saturated Si(001) surface is different from the structure of the biphenyl on the non saturated surface. With the adsorption of the biphenyl molecule on the Si(001) surface, the energy band gap suffer small changes. The presence of the biphenyl on the surface introduce energy levels inside de valence band and inside the conduction band. For non-passivated surfaces the band gap suffer very small reduction when the biphenyl is adsorbed. On the other hand for hydrogen passivated surfaces the band gap suffer an enlargement with the adsorption of the biphenyl molecule.